Analisis Pelayanan Fisioterapi Terhadap Kepuasan Pasien Rawat Jalan Reguler di Unit Rehabilitasi Medik di RSUD Dr. Moewardi - Widanarko, Arif, Dwi Astuti, S.Pd., M.Kes, Sri Darnoto, SKM., MPH (2013)
Traffic levels reflect overall hospital performance and high performance can be achieved because of patient satisfaction with hospital services DR. Moewardi especially in Medical Rehabilitation unit, then the decline in the number of visits can be an indicator of patients not achieving patient satisfaction with medical care in a hospital rehabilitation unit DR. Moewardi. The purpose of this study is knows the effect of physiotherapy services officer on patient satisfaction in the Hospital Medical Rehabilitation unit DR. Moewardi. The method of study used cross-sectional design to determine the relationship of the quality of physiotherapy services at the hospital DR Moewardi Surakarta on outpatients satisfaction. The population in this study were all outpatients at the physiotherapy hospital DR Moewardi Surakarta, samples used in this study were taken by the method of convenience sampling of 100 respondents in the sample. Statistical tests using multiple linear regression using SPSS 21. Results of the research showed that there is an influence of quality physiotherapy service personnel action against the level of patient satisfaction (p-value <0.05) with large variations in patient satisfaction rate changes by variations in quality of care measures changes in officer physiotherapy at 80.3%, while the remaining 19, 7% influenced by factors other than hospitality workers physiotherapy, physiotherapy attendant attention, courtesy officer physiotherapy, physiotherapy officer patience, and empathy physiotherapy officer.